Agricultural policies for the 1990s - Aziz, Sartaj (Development Centre of the Organisation for Economic Co-operation and Development, 1990)
Contents: Chapter 1. Introduction; Chapter 2. Policies for increasing agricultural production; Chapter 3. Policies for improving food security;... .